Imaginaries of the city from sensitive cartographies.: The case of Cuernavaca, Mexico (2021)
This article is the result of the analysis of the tour and workshop held in the city of Cuernavaca, Morelos, Mexico, on March 10, 2020; For these activities, the sensitive mapping methodology was used as a basis. The tour was carried out with inhabitants of the city of Cuernavaca, women and men whose ages range between 19 and 25 years. From this journey that began at the Roundabout of the Moon, an important urban node, and ended at the La Tallera Museum, a public space where contemporary art is exhibited, it was sought to recognize what the inhabitants feel when touring the city; in this sense, the subject and the body were considered as feelings, as defined by the sociologist Alicia Lindón (2009). During the tour, the participants identified symbolic elements, spaces or objects that help the orientation and “readability” of the city, as developed by urban planner Kevin Lynch (1984). The result of this sensitive observation and listening was a collective mapping carried out by the participants, which will be analyzed in this article from two approaches: the sensitivity of the subjects in space, where the perception of security was identified as fundamental, and the reading of space as a guiding, formal and functional entity, where commercial spaces stand out as reference elements.